Vancomycin Resistance pattern of Staphylococcus aureus Isolated from Skin and Soft Tissue Infections (SSTI) in Mosul City - Muna M. Isaam (College of Education for Pure Sciences, 2009)
ABSTRACT The present study includes the study of the inhibitory effect of vancomycin which has been used as the standard treatment for MRSA Staphylococcus aureus isolated from skin and soft tissue infections (SSTI). Results showed the appearance of resistant isolates 9(19.69 %). Intermediate 5 (10.86 %) and susceptible 32(69.56 %). The study also revealed that there was a relationship between antibiotic resistance and exfoliative toxin producing (ETS) isolated from hospitalized patients suffering severe epidermal lesions. The incidence of ETS resistant to vancomycin was 3 (6.52 %) of total strains.